ORNIPURAL® as conventional therapy versus mixture of Curcuma longa extract and pomegranate peel extract as homeotherapy in dogs with dexamethasone-induced hepatopathy: clinicolaboratory, ultrasonographic, and histopathological monitoring - Khalphallah, Arafat; Mousa, Sabry A.; Almuhanna, Abdulaziz H.; Hassan, Dalia; Al-Shuraym, Laila A.; Alkeridis, Lamya Ahmed; Abdel-lah, Ebtsam S.; Shukry, Mustafa; Abdelhafez, Enas A.; Elmeligy, Enas (Frontiers in Veterinary Science, 2025)
IntroductionCurcuma longa extract and pomegranate peel extract as homeotherapy have numerous therapeutic uses, mainly for anti-inflammatory, immunomodulatory, and hepatoprotective efficacy. The current study compared ORNIPURAL® (as a commercial hepatoprotective drug) and a herbal mixture of Curcuma longa extract and pomegranate peel extract [as homeotherapy] in dogs with dexamethasone-induced hepatopathy throughout a 42-day long-term study.MethodsThe study was conducted on mongrel dogs (n = 30) throughout three phases of the experiment: an acclimatization phase (14 days), a steroidal-induced hepatopathy phase (14 days), and a treatment phase (14 days, i.e., either with ORNIPURAL® or with herbal mixtures). The investigated dogs undergoing complete clinical and ultrasonographic examinations as well as hematological analysis and serum hepatorenal biomarkers that were estimated in days 0 (control group), 7 (hepatopathy group), 14 (hepatopathy group), 21 (treatment group), and 28 (treatment group). Histopathology of the liver was conducted for some dogs on days 0, 14, and 28 after the euthanization of these animals.Results and conclusionThe present study reported the most remarkable efficacy of both ORNIPURAL® and a herbal mixture of Curcuma longa extract and pomegranate peel extract as hepatoprotective medicaments in the therapy of dexamethasone-induced fatty liver in dogs. Therefore, a 14-day treatment with either a herbal mixture or ORNIPURAL® in treated dogs (treatment groups) induced an unmistakable improvement in their clinical status, blood pictures, and serum hepatorenal parameters as well as characteristic sonographic and histopathological findings compared with those in dexamethasone-induced hepatic lipidosis (hepatopathy groups). Compared to dogs treated with ORNIPURAL®, this clinical improvement was more evident in dogs treated with an herbal mixture. Moreover, no significant alterations in blood pictures and serum hepatorenal indices were demonstrated between ORNIPURAL® and herbal-treated dogs. Overall, the herbal mix of Curcuma longa extract and pomegranate peel extract had higher efficacy and greater potency than conventional therapy that uses ORNIPURAL® in treating dogs with hepatopathy. The study also recommended the parallel use of this herbal mixture as well as ORNIPURAL® in long-term therapeutic strategies in dogs with dexamethasone-induced fatty liver as both minimized dexamethasone side effects. Ultrasonography alone was not enough to evaluate hepatobiliary disorders in canines.